2014
DOI: 10.1177/0954405414553981
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of the ultrasonic cold forging technology process for improving surface mechanical properties of 6XB2C cold-worked alloy steel tool

Abstract: Ultrasonic cold forging technology is a mechanical process used to improve surface characteristics of materials by continual striking of the tool in a reciprocating motion. In this study, the proper geometrical shapes of the booster and the horn (collectively called ''the concentrator'') were obtained through numerous simulations based on the frequencies produced, the power of an ultrasonic generator (about 20 kHz), and the mechanical vibrations transferred parallel to the axis of the ultrasonic head (transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Table 1 denotes a summary of experimental data aimed at cold-formed steels. 1 Nominal steel yield strengthSuch studies on mechanical behavior of structural steels, again considering of exposure to the elevated temperatures, can be categorized into mild steel group and high strength steel (HSS). In this case and in another similar review study, Li et al [39] reported the test experimental data upon mechanical behavior of hot-rolled carbon structural steels at such elevated temperatures, with strength grades of 235-960 MPa.…”
Section: Novelty Of the Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 denotes a summary of experimental data aimed at cold-formed steels. 1 Nominal steel yield strengthSuch studies on mechanical behavior of structural steels, again considering of exposure to the elevated temperatures, can be categorized into mild steel group and high strength steel (HSS). In this case and in another similar review study, Li et al [39] reported the test experimental data upon mechanical behavior of hot-rolled carbon structural steels at such elevated temperatures, with strength grades of 235-960 MPa.…”
Section: Novelty Of the Studymentioning
confidence: 99%
“…Fig. 5 Peening function of the ultrasonic tool illustrated by Abbasi et al [1] (Redrawn by referring to the work by Abbasi et al [1] microstructure in the various plane diffraction directions. The diffraction profile measurements can be accomplished by the iterative electrolytical removal of thin surface layers as well as the subsequent XRD measurements.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations